2021
DOI: 10.1108/md-01-2021-0112
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of national culture on integrated report assurance: international evidence

Abstract: PurposeDrawing on neo-institutional, stakeholder, social contract and contingency theories, the objective of this study is to examine whether cultural values across countries may influence decisions to assure integrated reports.Design/methodology/approachFor this purpose, the authors have collected integrated reporting assurance, national culture and firm-specific data from several sources for the years ranging between 2011 and 2016 and have performed pooled and panel logistic regression analyses.FindingsThe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…Our results confirm that SMEs in countries with the following characteristics present a stronger tendency to assure sustainability information: lower power distance, stronger feminine versus masculine values and lower uncertainty avoidance. In general, these findings are in line with the previous literature (Gallén & Peraita, 2018;Romero & Fernandez-Feijoo, 2013;Uyar et al, 2021); however, uncertainty avoidance was found to be positive by Uyar et al (2021), while, here, individualism and long-term orientation have been found…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results confirm that SMEs in countries with the following characteristics present a stronger tendency to assure sustainability information: lower power distance, stronger feminine versus masculine values and lower uncertainty avoidance. In general, these findings are in line with the previous literature (Gallén & Peraita, 2018;Romero & Fernandez-Feijoo, 2013;Uyar et al, 2021); however, uncertainty avoidance was found to be positive by Uyar et al (2021), while, here, individualism and long-term orientation have been found…”
Section: Discussionsupporting
confidence: 93%
“…A number of different sociological variables have been the specific focus of study in this field of research (Martínez‐Ferrero & García‐Sánchez, 2017; Romero & Fernandez‐Feijoo, 2013; Uyar et al, 2021). Hofstede (1980) has characterised national culture in terms of four dimensions that have subsequently been widely employed in academic research: namely, (1) power distance, (2) individualism, (3) masculinity and (4) uncertainty avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a combination of theories was also noted. For example, Uyar et al (2021) draw on institutional, stakeholder, social contract and contingency theories to explain their results, while Briem and Wald (2018) use institutional, diffusion of innovation and agency theories to analyse their findings.…”
Section: Ro1: An Overview Of the Fieldmentioning
confidence: 99%
“…In terms of IRA, Kılıç et al (2020), in their multi-country study, documented that ethical business environments, less effective boards and weaker auditing and reporting standards Non-financial information assurance are positively correlated with decisions to secure IRA. Uyar et al (2021) also conducted a multi-country analysis and find that a collectivist culture, lower power distance and high uncertainty avoidance are positively associated with decisions to accept IRA. In comparison, masculine values, long-term orientation and a higher level of indulgence are negatively associated with decisions to accept IRA.…”
Section: A Tripartite Engagementmentioning
confidence: 99%
“…The authors explain that when investors seek information to plan their investment choices, they consider SRA adoption as an observable signal of business ethics, increasing their willingness to invest in the company. The study of Uyar et al (2021) focuses on Hofstede’s cultural dimensions. Their findings prove that companies based in collectivist societies are more likely to adopt SRA practices since they are more concerned about the impact of corporate activities on society when compared to companies from individualistic societies.…”
Section: Literature Review On Determinants Of Sustainability Reportin...mentioning
confidence: 99%